Driving-related behaviors, attitudes, and perceptions among Australian medical cannabis users: results from the CAMS 20 survey - Thomas R. Arkell; Sarah V. Abelev; Llewellyn Mills; Anastasia Suraev; Jonathon C. Arnold; Nicholas Lintzeris; Iain S. McGregor (BMC, 2023)
Abstract Road safety is an important concern amidst expanding worldwide access to legal cannabis. The present study reports on the driving-related subsection of the Cannabis as Medicine Survey 2020 (CAMS-20) which surveyed driving-related behaviors, attitudes, and perceptions among Australian medical cannabis (MC) users. Of the 1063 respondents who reported driving a motor vehicle in the past 12 months, 28% (297/1063) reported driving under the influence of cannabis (DUIC). Overall, 49-56% of respondents said they typically drive within 6 h of MC use, depending on the route of administration (oral or inhaled). Non-medical cannabis (NMC) was perceived to be more impairing for driving than MC. Binary logistic regression revealed associations between likelihood of DUIC and (1) inhaled routes of cannabis administration, (2) THC-dominant products, (3) illicit rather than prescribed use, (4) believing NMC does not impair driving, and (5) not being deterred by roadside drug testing. Overall, these findings suggest there is a relatively low perception of driving-related risk among MC users. Targeted education programs may be needed to highlight the potential risks associated with DUIC, and further research is needed to determine whether driving performance is differentially affected by MC and NMC.